1994
DOI: 10.1083/jcb.127.4.1021
|View full text |Cite
|
Sign up to set email alerts
|

Kinesin-mediated organelle translocation revealed by specific cellular manipulations.

Abstract: Abstract. The distribution of membrane-bound organelles was studied in cultured hippocampal neurons after antisense oligonucleotide suppression of the kinesin-heavy chain (KHC). We observed reduced 3,3'-dihexyloxacarbocyanine iodide (DiOC6(3)) fluorescent staining in neurites and growth cones. In astrocytes, KHC suppression results in the disappearance of the DiOC6(3)-positive reticular network from the cell periphery, and a parallel accumulation of label within the cell center. On the other hand, mitochondria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

14
102
3

Year Published

1996
1996
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(119 citation statements)
references
References 52 publications
14
102
3
Order By: Relevance
“…These contradictory movements of Golgi elements are mediated by distinct molecular motors. Consistent with earlier findings by Feiguin et al (1994), who found that the expression of kinesin antisense oligonucleotide rendered the Golgi apparatus more compact, microinjection of antikinesin antibodies inhibited Golgi dispersion along stable, nocodazole-resistant MTs (Minin, 1997). Conversely, the central localization of the Golgi apparatus involves cytoplasmic dynein (Corthésy-Theulaz et al, 1992;Fath et al, 1994;Burkhardt et al, 1997;Harada et al, 1998).…”
supporting
confidence: 80%
“…These contradictory movements of Golgi elements are mediated by distinct molecular motors. Consistent with earlier findings by Feiguin et al (1994), who found that the expression of kinesin antisense oligonucleotide rendered the Golgi apparatus more compact, microinjection of antikinesin antibodies inhibited Golgi dispersion along stable, nocodazole-resistant MTs (Minin, 1997). Conversely, the central localization of the Golgi apparatus involves cytoplasmic dynein (Corthésy-Theulaz et al, 1992;Fath et al, 1994;Burkhardt et al, 1997;Harada et al, 1998).…”
supporting
confidence: 80%
“…However, function disruption tests have again yielded conflicting data. Antisense oligonucleotide inhibition of KHC in cultured rat astrocytes caused a retraction of the ER network (Feiguin et al, 1994). In contrast, antibody inhibition of KHC in sea urchin embryonic cells (Wright et al, 1993) or gene disruption in mouse extraembryonic cells (Tanaka et al, 1998) had no dramatic effects on ER organization.…”
Section: Discussionmentioning
confidence: 96%
“…For example, in a study of vesicle/ tubule transport in the recycling pathway, antibody inhibition of KHC blocked brefeldin A-induced movement of Golgi membranes into the ER in cultured NRK cells (Lippincott-Schwartz et al, 1995). Conversely, antisense oligonucleotide inhibition of KHC in cultured rat astrocytes (Feiguin et al, 1994) and gene disruption in cultured mouse extraembryonic cells (Tanaka et al, 1998) did not prevent brefeldin A-induced Golgi-to-ER membrane transfer. With regard to Golgi-to-plasma membrane vesicle transport, antisense oligonucleotide inhibition of KHC in cultured vertebrate neurons impaired delivery of vesicles containing certain synaptic proteins to axon terminals (Ferreira et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations